A dynamic data driven optimization system for yard crane management - Guo, Xi. (2012)
Breakdown of trade barriers and the trend of globalization have greatly increased the importance of marine transportation systems and container terminals, which serve as hubs and are crucial links of the marine transportation network. Nowadays, the number of container transshipment is burgeoning. There are increased competition between seaports and higher demands on container terminal logistics and operation management systems.